PEMANFAATAN KRIB UNTUK PENGGELONTORAN SEDIMEN PADA MUARA SUNGAI (STUDI KASUS MUARA SUNGAI JUWANA) - Jati Widhiasmoro; Perdana Gutomo Putra; Salamun Salamun; Abdul Kadir (Jurnal Karya Teknik Sipil, 2013)
Sedimentation is often happen in low-ground area. Where the minimum slope of the river caused a low-velocity in river flow. A low-velocity flow made the particles of sand drownded to the river bed because of the gravity. Low-velocity flow also cause by the tide of sea. It is why sedimentation is happen in estuary.In Juwana river case, using SMS 8.1 software with RMA2 model, on the highest tide, with the quantity of river-flow is 100 m3/s gained 0,15 m/s of the river velocity. Based on Hjulstorm diagram (Sundborg modification), with this velocity of river flow, will cause a sediment of anykind sand-particle.  Placing 6 of 45x45 square piles, 2 m between each pile on formation and placed every 50 m along side the river and when the river quantity is 100 m3/s at the highest tide, give a significant additional speed. It will rising the velocity up between 0,14 to 0,17 m/s.  In other word, the velocity of Juwana river becomes 0,29 m/s to 0,32 m/s, which is high enough to flush a fine-sand sediment.